Štúdium vplyvu chloridov a bromidov na kritickú micelovú koncentráciu a parciálny mólový objem kvartérnej amóniovej soli - Salanci, Eva; Andriamainty, Fils; Adamove, Dominika; Mikláš, Roman (Chemické listy, 2022)
The critical micelle concentration (CMC) of the selected surfactant belonging to quaternary ammonium salts with chemical designation N,N-dimethyl-N-(3-((1R,5S)-1,8,8-trimethyl-2,4-dioxo-3-azabicyclo[3.2.1]octane-3yl)propyl)hexadecane-1-amine bromide was determined. Simultaneously, the effect of the addition of various concentrations of NaCl, KCl, NaBr, and KBr salts on the CMC value of the substance was observed and compared with those obtained in an aqueous solution at T = 296,15 K. Based on the results obtained, it was concluded that NaCl and KCl salts decreased the critical micelle concentration, while NaBr and KBr salts did not support micellization and CMC values therefore increased. In the case of solutions of a substance in the salt environment, when compared to the substance's solution in distilled water, a decrease in partial molar volume was observed. From the concentration density dependencies of the substance, an ionization degree of α was determined. Finally, the molar Gibbs energy ∆G° was also calculated and found negative for all salt solutions, while increase with their increasing concentration.
Keywords: výzkum; Ammonium Compounds; amoniové sloučeniny; Research; Disinfectants; dezinficiencia